2021
DOI: 10.3389/fnut.2021.734991
|View full text |Cite
|
Sign up to set email alerts
|

Improving Healthy Food Choices in Low-Income Settings in the United States Using Behavioral Economic-Based Adaptations to Choice Architecture

Abstract: Low diet quality is a significant public health problem in the United States, especially among low-income populations. The food environment influences dietary choices. When applied to eating behavior, behavioral economics (BE) recognizes that decision biases instigated by a food environment saturated with unhealthy foods may lead people to purchase such foods, even when they possess the necessary information and skills to make healthy dietary choices. Choice architecture, a BE concept that involves modifying t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…Although the data for all of the food purchases made during this study were not collected, these findings are encouraging when examining innovative strategies to improve food access, nutritional intake, and ultimately the health status of rural and SNAP populations, who generally have disproportional high rates of diet-related chronic diseases, in part due to nutritional inadequacy. Furthermore, previous studies have attempted to target these populations and improve purchasing habits utilizing behavior nudging principles to modify behaviors [ 17 , 29 , 35 ]. However, as online grocery shopping continues to grow as an engagement method, these principles can be applied to an online landscape rather than an in-store approach alone in an effort to improve purchases [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the data for all of the food purchases made during this study were not collected, these findings are encouraging when examining innovative strategies to improve food access, nutritional intake, and ultimately the health status of rural and SNAP populations, who generally have disproportional high rates of diet-related chronic diseases, in part due to nutritional inadequacy. Furthermore, previous studies have attempted to target these populations and improve purchasing habits utilizing behavior nudging principles to modify behaviors [ 17 , 29 , 35 ]. However, as online grocery shopping continues to grow as an engagement method, these principles can be applied to an online landscape rather than an in-store approach alone in an effort to improve purchases [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several SNAP interventions conducted in grocery stores indicated that shoppers make more nutritious choices when multiple nudges are utilized. Specifically, a systematic review indicated that behavioral economic strategies, such as nudges of easy to understand quick nutrition information, improve purchases of fruits and vegetables [ 17 ]. Several studies using choice architecture constructs, such as changing the store layout and the prominent positioning of healthy foods, improved purchases of healthier foods among those customers [ 5 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that behavioral economics strategies to make healthier food choices more appealing and easier are effective in food banks and pantries. There is evidence that the Supporting Wellness at Pantries (SWAP) traffic-light labeling system [ 79 ] can help food pantry staff procure healthier food options [ 80 ] and that placing healthier foods in more prominent locations (e.g., eye-level) results in healthier consumption [ 81 •].…”
Section: Community-based Programsmentioning
confidence: 99%
“…In recent years, charitable food agencies, including both food pantries and food banks, have increasingly devoted efforts to promote healthy food [ 1 , 2 , 29 ]. These efforts include implementing nutrition policies for their food inventory; offering nutrition education programs for their clients; improving the supply of healthy food within the system; and integrating behavioral economic strategies to promote healthy food selection at the food pantry [ 1 , 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%